Pengaruh Pelatihan dan Motivasi Kerja terhadap Kinerja Mitra Lapangan Badan Pusat Statistik Kota Sukabumi - Sri Rahamati; Eris Juliasnyah (Universitas Linggabuana PGRI Sukabumi, 2022)
This research aims to find out how training and work motivation contribute to the performance of field partners in the Central Bureau of Statistics for the City of Sukabumi. In accordance with the purpose of researchers using the associative method with a quantitative approach. The population is Field Partners of the Central Bureau of Statistics for the City of Sukabumi, totaling 150 people. Because the population size of 150 is large enough for the researcher, the researcher uses the sample method with the solvin formula and obtains 110 samples. The analytical method includes data quality tests, analysis prerequisite tests, multiple linear regression analysis tests, analysis of the coefficient of determination and hypothesis testing using SPSS statistical program version 26. The results of training and work motivation positively and significantly contributed to the performance of field partners at the Central Bureau of Statistics for the City of Sukabumi.